1998
DOI: 10.1002/(sici)1098-2272(1998)15:1<103::aid-gepi8>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

FRAXA and FRAXE prevalence in patients with nonspecific mental retardation in the Hellenic population

Abstract: Mutations at FRAXA and FRAXE loci are due to expansions of a CGG trinucleotide repeat and are characterized by mental retardation. Here we report a pilot screening survey by means of cytogenetic and molecular methods of 433 unrelated retarded individuals and their parents of Hellenic origin coming from various parts of Greece and Cyprus. The purpose of the study was to estimate the frequency of FRAXA mutation in individuals with nonspecific mental retardation without family history and phenotypic stigmata in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…1). Thus, prevalence of FXS full mutation in this high-risk population from Central Java, Indonesia, is 4.0% (1.1% in males and 7.1% in females; 95% confidence interval (2.0%, 8.1%) in agreement with reports from previous studies in other populations) (Sutherland, 1985;Syrrou et al, 1998;de Vries et al, 1999;Faradz et al, 1999;Pouya et al, 2009). However, the FXS full mutation was 0.72% (1/139) in the ID populations alone.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1). Thus, prevalence of FXS full mutation in this high-risk population from Central Java, Indonesia, is 4.0% (1.1% in males and 7.1% in females; 95% confidence interval (2.0%, 8.1%) in agreement with reports from previous studies in other populations) (Sutherland, 1985;Syrrou et al, 1998;de Vries et al, 1999;Faradz et al, 1999;Pouya et al, 2009). However, the FXS full mutation was 0.72% (1/139) in the ID populations alone.…”
Section: Resultssupporting
confidence: 90%
“…A number of studies have been carried out in populations of individuals with IDs, with a prevalence varying from *1% to 6.3% (Sutherland, 1985;Syrrou et al, 1998;de Vries et al, 1999;Faradz et al, 1999;Pouya et al, 2009). A previous study in Indonesia showed an FXS prevalence of 1.9% among the ID population (Faradz et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Employing the DNA diagnostic methods, another report from Southern India revealed a frequency of 7%, comparable to our results [Baskaran et al, 1998]. However, we cannot compare our results with those reported for most other Western institutionalized populations, which included all unexplained MR cases in their study samples [Meadows et al, 1996;Mila et al, 1997;Elbaz et al, 1998;Syrrou et al, 1998;Crawford et al, 1999;Pang et al, 1999;Patsalis et al, 1999]. Considering the stringent selection criteria employed in this study, the overall frequency of FXS in India may be very similar to that reported for other Western and Asian populations [Patsalis et al, 1999].…”
Section: Discussionsupporting
confidence: 84%
“…In the majority of patients with FRAXA, full mutations have been reported in the literature among patients with mild to moderate mental retardation (Jacobs et al, 1993;Wang et al, 1993;Hofstee et al, 1994;Buttler et al, 1995;De Vries et al, 1997 salis et al, 1997;Baskaran et al, 1998;Syrrou et al, 1998). A recent review points out that only 3% of FRAXA patients were among the moderate to severe mental retardation group (Knight et al, 1999).…”
Section: Discussionmentioning
confidence: 99%